2020
DOI: 10.5114/aic.2020.101769
|View full text |Cite
|
Sign up to set email alerts
|

Female gender and the clinical and periprocedural profile and clinical outcomes of transcatheter aortic valve implantation: experiences of a tertiary Polish centre

Abstract: Introduction Despite the establishment of multiple factors influencing short- and mid-term outcomes in patients treated with transcatheter aortic valve implantation (TAVI), the real-world data on the association between gender and outcomes after TAVI remain conflicting. Aim To evaluate the association of female gender with the clinical and periprocedural characteristics along with in-hospital, short- and medium-term outcomes of patients treated with TAVI in comparison w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…AKI was reported in 14 studies, 16–18,21,22,24,29,31,32,35,37,38,41,42 with significantly higher rates of AKI found in males in 3 studies. 17,22,29 Rates of AKI in these studies ranged from 3.66% to 26% and 2.13% to 14% for males and females, respectively ( P = 0.04–0.001).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…AKI was reported in 14 studies, 16–18,21,22,24,29,31,32,35,37,38,41,42 with significantly higher rates of AKI found in males in 3 studies. 17,22,29 Rates of AKI in these studies ranged from 3.66% to 26% and 2.13% to 14% for males and females, respectively ( P = 0.04–0.001).…”
Section: Resultsmentioning
confidence: 98%
“…A total of 28 16–43 studies were included that investigated the differences in outcomes between males and females undergoing TAVR. All included studies had a combined total of 156 275 patients with data collection dates ranging from 2004 to 2020.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations